ANALISIS BEBERAPA FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG KAKI LIMA PEREMPUAN DI KOTA DENPASAR - Lismalasari, Erika; Aswitari, Luh Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 3 (2021): VOL 10 NO 3,MARETI 2021 [ 899 - 1330], 2021)
Women is one indicator the success of achieving the country's development. This shows that increasing contribution of women the strategies in the problem of poverty. The objectives in this study are 1) analyze effect of work experience, age, and number of children on work hours, 2) analyze effect of work experience, age, number of children, and work hours on income, 3) analyze work hours spent in mediating the effect of work experience, age, and number of children on income. Respondents were 123 samples with non-probability sampling. Analysis technique used path analysis. The results of this study stated that 1) work experience and the number of children had a positive and significant effect, but age had a negative and significant effect on outflow of working hours, 2) work experience and the number of children had a positive and significant effect, but age had a negative and significant effect on income and 3) the role of outpouring of work hours mediates the effect of work experience and the number of children, but does not mediate the effect of age on the income of female street vendors in the city of Denpasar.   Keywords: work experience, age, number of children, hours spent working, income.